2021
DOI: 10.3389/fpsyg.2021.630058
|View full text |Cite
|
Sign up to set email alerts
|

Female Micro-Entrepreneurs and Social Networks: Diagnostic Analysis of the Influence of Social-Media Marketing Strategies on Brand Financial Performance

Abstract: The business world is facing a very complicated situation due to the COVID-19 pandemic. Small- and medium-sized companies (SMEs)—both in Spain and at the global level—are seeing their survival jeopardized by a fall in revenues. This scenario is aggravated in the case of micro-SMEs headed by female entrepreneurs. Accordingly, micro-SMEs, particularly those led by female entrepreneurs, need to reinvent themselves to overcome the current adversities that could lead to the destruction of their businesses and hence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 54 publications
1
12
0
1
Order By: Relevance
“…These findings are consistent with earlier research which showed that the use of social networks and web presence for business purposes has a positive effect on the digital transformation of SMEs. Digital transformation is achieved through online marketing and easing the communication process between buyers and sellers [17,32,48,53]. Surprisingly, the effect of E-commerce adoption on perceived digital transformation was found to be statistically insignificant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings are consistent with earlier research which showed that the use of social networks and web presence for business purposes has a positive effect on the digital transformation of SMEs. Digital transformation is achieved through online marketing and easing the communication process between buyers and sellers [17,32,48,53]. Surprisingly, the effect of E-commerce adoption on perceived digital transformation was found to be statistically insignificant.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it is evident from recent research that the educational attainment of female entrepreneurs strengthened the positive impact of digital transformation on the financial performance of SMEs during the COVID-19 pandemic [32]. Therefore, targeted training for women business owners/managers could enhance their critical thinking and communication skills further, which are indispensable for decision-making during periods of crisis such as COVID-19.…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, to gain a deeper understanding of the interactions [83][84][85], we plotted the moderation effect of environmental and governance pillar scores to the traditional variable. Following the literature, we adopted the approach suggested by Dawson and Richter [86], and we graphed both interactions [87].…”
Section: Moderation Effects Of Egs Factorsmentioning
confidence: 99%
“…Some studies also discuss transformation drivers in business during Covid-19 as the potential strategic process to cope with the crisis era. For example, transformation in an organization (Muñoz-pascual, 2021;Nurunnabi, 2020); Technology (Jiménez-zarco et al, 2021;Nuseir & Aljumah, 2020;Winarsih et al, 2021); Consumer behavior (Harahap et al, 2020); Financial (Klein & Todesco, 2021;Moretto & Caniato, 2021), External Support (Falahat et al, 2021), Network relationship (Adam et al, 2020;Arsik et al, 2018;Guan et al, 2020;Ivanov, 2020;Ivanov and Dolgui 2020;Guan et al, 2020;Meqdadi et al, 2020;Saputra et al, 2021;Siu, 2016;Sodhi, 2016;Utomo et al, 2020), and as the benchmark business performance .…”
Section: Business Transformationmentioning
confidence: 99%